Comparison of the effect of thought distraction by music therapy and the presence of caregiver on anxiety level of patients undergoing endoscopy - Zakieh Ahmadi; Afsaneh Alaei Sheikh Robat; Saeed Hosseini Teshnizi; Reza Jamhiry; Aref Faghih (Tehran University of Medical Sciences, 2021)
Background & Aim: Stress and anxiety are one of the major problems in patients undergoing semi-invasive and invasive procedures such as endoscopy. Different methods to reduce anxiety do not have the same effects. The aim of this study is to compare the effect of thought distraction by music therapy and the presence of caregiver on anxiety level of patients undergoing endoscopy. Methods & Materials: In this randomized clinical trial, 105 patients referred to endoscopy ward of Shahid Mohammadi hospital and Persian Gulf Bandar Abbas hospital in 2018 were selected by the convenience sampling method and assigned into three groups of music therapy, presence of caregiver and control using the random allocation (35 in each group). The demographic information form and the Spielberger anxiety questionnaire (STAL) were completed before and after the intervention. In the music therapy group, patients received natural sounds through headphones. In the caregiver's presence group, endoscopy was performed with the presence of caregiver, and the control group only received routine pre-endoscopic care. Data were analyzed using descriptive and inferential statistics through the SPSS software version 24 at a significance level of 0.05. Results: The result of analysis of variance showed that there was no significant difference in the anxiety mean score between the three groups before the intervention (P=0.77), but a significant difference was observed after the intervention (P<0.005). The decrease in scores in the music therapy group was significant (P=0.044), but in the caregiver's presence group (P=0.571) and the control group (P=0.663), no significant change was observed before and after endoscopy. Conclusion: The results of this study showed that distraction with music therapy is an effective way to help patients undergoing endoscopy, and the use of this method can help the procedure to be performed better and enhance patient satisfaction. Clinical trial registry: IRCT20190715044215N1